SCIENCE WRITING HEURISTIC: TO ENHANCE STUDENTS' COMMUNICATION AND RESEARCH SKILL - Silva Fadilah Suparman; Nurani Hadnistia Darmawan (STKIP Subang, 2022)
The 21st century paradigm requires humans to develop various skills, including communication skills and research skills. In the context of learning activities, the importance of mastering communication skills is that students can express their thoughts, ideas, knowledge, or new information in the form of verbal and non-verbal. The importance of developing research skills is that research activities can stimulate critical thinking and problem solving skills. The purpose of this study was to improve written communication skills and research skills of prospective teacher students at STKIP Bina Mutiara Sukabumi by implementing the Science Writing Heuristic (SWH) approach. This study used a pre-experimental method with a single group pre-test post-test design. The research instrument used was a subjective test in form of essay consisted of 14 items, with details of 4 items derived from indicators of written communication skills and 10 items derived from indicators of research skills. The sample of this research was 15 students of STKIP Bina Mutiara Sukabumi. The results showed that students' written communication skills and research skills improved by using the SWH approach. The results of the t-test conducted were 0.00 < α = 0.05, indicating that the SWH approach had a significant effect on students' written communication skills and research skills. The gain test results obtained an n-gain value of 0.456 for written communication skills and 0.501 for research skills which indicated that the increase in both skills was in the